Lipocalin-2 Functions as Inhibitor of Innate Resistance to Mycobacterium tuberculosis - Dahl, Sara Louise; Woodworth, Joshua S.; Lerche, Christian Johann; Cramer, Elisabeth Præstekjær; Nielsen, Pia Rude; Moser, Claus; Thomsen, Allan Randrup; Borregaard, Niels; Cowland, Jack Bernard (Frontiers in Immunology, 2018)
Lipocalin-2 is a constituent of the neutrophil secondary granules and is expressed de novo by macrophages and epithelium in response to inflammation. Lipocalin-2 acts in a bacteriostatic fashion by binding iron-loaded siderophores required for bacterial growth. Mycobacterium tuberculosis (M.tb) produces siderophores that can be bound by lipocalin-2. The impact of lipocalin-2 in the innate immune response toward extracellular bacteria has been established whereas the effect on intracellular bacteria, such as M.tb, is less well-described. Here we show that lipocalin-2 surprisingly confers a growth advantage on M.tb in the early stages of infection (3 weeks post-challenge). Using mixed bone marrow chimeras, we demonstrate that lipocalin-2 derived from granulocytes, but not from epithelia and macrophages, leads to increased susceptibility to M.tb infection. In contrast, lipocalin-2 is not observed to promote mycobacterial growth at later stages of M.tb infection. We demonstrate co-localization of granulocytes and mycobacteria within the nascent granulomas at week 3 post-challenge, but not in the consolidated granulomas at week 5. We hypothesize that neutrophil-derived lipocalin-2 acts to supply a source of iron to M.tb in infected macrophages within the immature granuloma, thereby facilitating mycobacterial growth.